2019
DOI: 10.21640/ns.v11i23.2115
|View full text |Cite
|
Sign up to set email alerts
|

Community size, perception of health, depression and diabetes mellitus in Mexican adults

Abstract: Introduction: Type 2 Diabetes Mellitus is a public health problem. Theoretical approaches that include factors of the individual, environmental factors and the synergy of these variables in the development of T2D are necessary, to achieve a better understanding of the phenomenon. The research question was: What individual and environmental factors explain the presence of diabetes in a representative sample of the adult population of Mexico?             Method: Data from the Mexican Health and Aging Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Para totalizar el puntaje, todas las respuestas son sumadas y se considera que, a mayor puntaje, mayor es la percepción de factores de riesgo para desarrollar DT2. Se convirtió en una escala de 0 a 100 para mejorar la comprensión de los resultados, siendo Bajo= 0 -33.3; Moderado= 33.4 -66.7 y Alto= 66.8-100 (La construcción del índice de 0 a 100 ha sido utilizado en otras investigaciones que utilizan este mismo instrumento) 12,16 . El alfa de Cronbach fue 0.76, lo cual se considera confiable.…”
Section: Metodologíaunclassified
See 1 more Smart Citation
“…Para totalizar el puntaje, todas las respuestas son sumadas y se considera que, a mayor puntaje, mayor es la percepción de factores de riesgo para desarrollar DT2. Se convirtió en una escala de 0 a 100 para mejorar la comprensión de los resultados, siendo Bajo= 0 -33.3; Moderado= 33.4 -66.7 y Alto= 66.8-100 (La construcción del índice de 0 a 100 ha sido utilizado en otras investigaciones que utilizan este mismo instrumento) 12,16 . El alfa de Cronbach fue 0.76, lo cual se considera confiable.…”
Section: Metodologíaunclassified
“…Tradicionalmente, la revisión de literatura indica que existen factores relacionados con el riesgo de desarrollar DT2, tales como, el sedentarismo, el sobrepeso, la obesidad, la herencia genética, hipertensión arterial 7 ; sin embargo, en últimos años a partir de la perspectiva socio ecológica, que contempla la influencia de factores inmersos en los procesos y estructuras sociales sobre el estado de salud y enfermedad de las personas y algunas otras posturas como los determinantes sociales en salud, se ha observado que existen factores sociales y contextuales circundantes al individuo, como la zona rural/urbana, apoyo social/comunitario, espacios verdes, la inseguridad alimentaria, la globalización, el crecimiento urbano, entre otras, que pueden exacerbar el riesgo de desarrollar DT2 8,9,10,11,12,13 .…”
Section: Introductionunclassified
“…This is particularly worrisome for Mexico, given Type-II diabetes mellitus in the country has increased over several years from a prevalence of 9.2% in 2012 to 10.3% in 2018 [2,3]. In 2019, the Mexican Health and Aging Study found that individuals living with diabetes were more likely to experience severe depressive symptoms and issues sleeping [4]. Similarly, among 820 Mexican outpatients living with diabetes, investigators found a prevalence of depression to be 48.3%, while the anxiety disorder rate was 55.1% [5].…”
Section: Introductionmentioning
confidence: 99%